Neuroscience Approach in The Industrial Revolution 4.0 - Nuryunita Dewantari; Suwito Singgih (Indonesian Journal of Science and Education, 2022)
Industrial revolution 4.0 is related to the rapid progress of technology in the world. In short, the industrial revolution 4.0 is a digital transformation. In the face of the era of industrial revolution 4.0 as it is today, a neuroscience approach to the practical management of education is needed. The application of neuroscience can form synergy and engagement with high added value. This study provides an overview of the role of neuroscience approaches in the era of industrial revolution 4.0. The research method used in this study is a literature study. Based on the results of the research study shows that the neuroscience approach can maximize the theatre of the student's brain, which consists of emotional, social, cognitive, physical, and reflection aspects.